(untitled) (Annals of Medical Research, 2024)
Aim: This study aims to determine smoking status among primary school parents and identify factors influencing smoking cessation. Additionally, the study seeks to increase awareness about the transtheoretical model and examine its role in the smoking cessation process. Materials and Methods: The study was conducted with 2,354 parents of students from a primary school in Konya. Participants completed surveys assessing smoking status, attitudes towards quitting, and levels of awareness. Factors related to smoking status, including age, gender, education level, occupation, and alcohol use, were analyzed. Smokers quit attempts were associated with the stages of the transtheoretical model, and whether they sought professional help was evaluated. Results: Of the participants, 33.1% (n=780) were smokers. The average age of smokers was 36.6±4.61, and the frequency of smoking was higher among men than women. 39% of the participants were low-level smokers. Significant associations were observed between smoking status and factors such as age, gender, education level, occupation, and alcohol use (p<0.001). The majority of smokers attempted to quit using the "sudden cessation" method, with a low rate of seeking professional help. Most of those who successfully quit also used the "sudden cessation" method. 31.4% of participants had never attempted to quit smoking. As the number of quit attempts increased, participants were observed to become more prepared to quit smoking (p<0,001). According to the transtheoretical model, most individuals were in the precontemplation stage. Conclusion: The frequency of smoking is higher among men and decreases as education level increases. Most participants attempted to quit smoking on their own, with a low level of seeking professional help. Multiple attempts to leave have been shown to increase the likelihood of success, and awareness of the harms of passive smoking has significantly influenced smoking behavior.